2011
DOI: 10.1021/jf103915y
|View full text |Cite
|
Sign up to set email alerts
|

3-Sulfanylhexanol Precursor Biogenesis in Grapevine Cells: The Stimulating Effect of Botrytis cinerea

Abstract: Volatile thiols, compounds that contribute strongly to the varietal aroma, are present in much higher concentrations in sweet wines than in dry wines. This positive effect, due to the presence of Botrytis cinerea on the berries, in fact results from a strong enrichment of cysteine S-conjugate precursors in botrytized berries. In the present study, a convenient model was investigated to reproduce and therefore study this phenomenon. A Vitis vinifera cell culture was used as a simple model, and we focused on S-3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
50
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(56 citation statements)
references
References 32 publications
3
50
0
1
Order By: Relevance
“…When tested in a cell culture medium, the combination of the plant cells, B. cinerea and Glut-3MH resulted in a 250-fold higher increase in Cys-3MH concentration when compared to the plant cells and Glut-3MH with no fungus infection (Thibon et al, 2011). A decrease in concentration was observed in the continued presence of the fungus.…”
Section: Precursors Of Volatile Thiolsmentioning
confidence: 87%
See 3 more Smart Citations
“…When tested in a cell culture medium, the combination of the plant cells, B. cinerea and Glut-3MH resulted in a 250-fold higher increase in Cys-3MH concentration when compared to the plant cells and Glut-3MH with no fungus infection (Thibon et al, 2011). A decrease in concentration was observed in the continued presence of the fungus.…”
Section: Precursors Of Volatile Thiolsmentioning
confidence: 87%
“…This reaction could be induced by the grape berry enzymes (endogenous) or the grape microflora enzymes (exogenous). Work done by Thibon et al (2011) has in fact shown increased Cys-3MH concentrations in overripe fruit infected with the B. cinerea fungus. Coetzee (2011) investigated the effect of oxidation of Sauvignon blanc juice prior to fermentation in the presence of moderate concentrations of SO 2 .…”
Section: Effects Of Winemaking Processes On Volatile Thiol and Precurmentioning
confidence: 95%
See 2 more Smart Citations
“…The botrytization process increased the P-3SH level in grapes ~100-fold in 1 week, compared to healthy grapes. 15 The production pathway of this molecule was elucidated by Thibon et al 16 In model experiments using cell cultures, it was demonstrated that grapevine cells were able to produce P-3SH and that the presence of B. cinerea considerably increased the precursor level (up to 1,000-fold).…”
mentioning
confidence: 99%